Adult Neandertal clavicles from the El Sidrón site (Asturias, Spain) in the context of Homo pectoral girdle evolution. Issue 95 (June 2016) - Rosas, Antonio; Rodriguez-Perez, Francisco Javier; Bastir, Markus; Estalrrich, Almudena; Huguet, Rosa; García-Tabernero, Antonio; Pastor, Juan Francisco; de la Rasilla, Marco
Abstract: We undertook a three-dimensional geometric morphometric (3DGM) analysis on 12 new Neandertal clavicle specimens from the El Sidrón site (Spain), dated to 49, 000 years ago. The 3DGM methods were applied in a comparative framework in order to improve our understanding of trait polarity in features related to Homo pectoral girdle evolution, using other Neandertals, Homo sapiens, Pan, ATD6-50 ( Homo antecessor ), and KNM-WT 15000 ( Homo ergaster/erectus ) in the reference collection. Twenty-nine homologous landmarks were measured for each clavicle. Variation and morphological similarities were assessed through principal component analysis, conducted separately for the complete clavicle and the diaphysis. On average, Neandertal clavicles had significantly larger muscular entheses, double dorsal curvature, clavicle torsion, and cranial orientation of the acromial end than non-Neandertal clavicles; the El Sidrón clavicles fit this pattern. Variation within the samples was large, with extensive overlap between Homo species; only chimpanzee specimens clearly differed from the other specimens in morphometric terms. Taken together, our morphometric analyses are consistent with the following phylogenetic sequence. The primitive condition of the clavicle is manifest in the cranial orientation of both the acromial and sternal ends. The derived condition expressed in the H. sapiens  + Neandertal clade is defined by caudal rotation of both the sternal and acromial ends, but with variation in the number of acromia remaining in a certain cranial orientation. Finally, the autapomorphic Neandertal condition is defined by secondarily acquired primitive cranial re-orientation of the acromial end, which varies from individual to individual. These results suggest that the pace of phylogenetic change in the pectoral girdle does not seem to follow that of other postcranial skeletal features.